Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Di Digimap Sogo Kota Kasablanka - Rizky Malik Pebrianto; Anah Furyanah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of price and promotion on purchasing decisions at Digimap Sogo Kota Kasablanka, both partially and simultaneously. This type of research uses an associative quantitative method. The sampling technique uses random sampling with the Slovin technique, so that 97 consumers were obtained as respondents. The results of the analysis show that the Price value partially has a positive but insignificant effect on purchasing decisions. This is evidenced by the t-count value = 1.071 <t table 2.366 with a significance of 0.287> 0.05. Thus, H0H_0H0 is accepted and HaH_aHa is rejected, meaning that there is no significant effect between Price (X₁) on Purchasing Decisions (Y) at Digimap Sogo Kota Kasablanka. Promotion partially has a positive and significant effect on purchasing decisions. This is evidenced by the t-count value of 7.348> 2.366 and a significance of 0.000 <0.01. Thus, H0H_0H0 is rejected and HaH_aHa is accepted, meaning that there is a positive and significant influence between Promotion (X₂) on Purchasing Decisions (Y) at Digimap Sogo Kota Kasablanka. Price and promotion simultaneously have a positive and significant influence on purchasing decisions. This is evidenced by the Fcount value of 73.257> Ftable 3.94 at a significance level of 0.05 with a degree of freedom of the numerator (df1) of 1 and the denominator (df2) of 94. In addition, the significance value of 0.000 <0.01 also indicates that Ho is rejected and Ha is accepted. The Adjusted R2 value of 0.601 indicates that price and promotion contribute 60.1% to purchasing decisions, while the remaining 39.9% is influenced by other variables not studied.